ANALISIS PUTUSAN MAHKAMAH KONSTITUSI NOMOR 5/PUU-X/2012 TENTANG PENGUJIAN PASAL 50 AYAT (3) UNDANG-UNDANG NOMOR 20 TAHUN 2003 TENTANG SISTEM PENDIDIKAN NASIONAL - K.A. Noviansyah; K.M. Faisal Reza (Jurnal Cakrawala Ilmiah, 2023)
International standard education units give rise to discrimination and castration in the field of education, this violates the rights of citizens, especially for students who come from modest or underprivileged families, although this program does provide quotas for poor students who excel but this is questionable how with students who do not excel, they also have the right to get a proper education. This research is a normative research, with the types and sources of legal materials from secondary data. The technique of collecting legal material through literature study, with a deductive conclusion drawing technique. The results of this study are, the consideration of the Constitutional Court in Decision Number 5/PUU-X/2012 regarding the Request for Judicial Review of Article 50 Paragraph (3) of Law Number 20 of 2003 concerning the National Education System, is that there is a difference between RSBI/SBI and schools that not RSBI/SBI, in terms of facilities and infrastructure, financing, and educational output, will result in different treatment between these schools, including their students. This treatment is contrary to constitutional principles which mandate equal treatment between schools and between students, especially since the schools that are affected are government-owned schools. The implication of this decision is that all RSBI schools have the status of regular schools, supervised by the Provincial/District/City governments; all nameplates, letterheads, and RSBI school stamps cannot be used; prohibition of withdrawing RSBI program levies; implementing regular school financing management.